2018
DOI: 10.1186/s12890-018-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, burden and risk factors associated with bronchial asthma in commonwealth of independent states countries (Ukraine, Kazakhstan and Azerbaijan): results of the CORE study

Abstract: BackgroundIn the Commonwealth of Independent States (CIS) countries epidemiology of Bronchial Asthma (BA) is poorly characterized. The objective of this analysis is to present the prevalence, burden and risk factors associated with BA in the CIS countries as part of the CORE study (Chronic Obstructive REspiratory diseases).MethodsA total of 2842 adults (≥18 years) were recruited (964 in Kiev, Ukraine, 945 in Almaty, Kazakhstan, and 933 in Baku, Azerbaijan) in 2013–2015 during household visits. A two-step clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Asthma is quite a common but non-reportable disease due to which many asthmatic patients remain undiagnosed. According to an epidemiological study conducted in Russia, only 6.9% of the adults were previously diagnosed with asthma, whereas 25.7% of that same population reported asthma symptoms like wheezing or breathlessness that were not diagnosed earlier in their life [56] .…”
Section: Epidemiology and Different Factors Influencing Type-2 Asthmamentioning
confidence: 99%
“…Asthma is quite a common but non-reportable disease due to which many asthmatic patients remain undiagnosed. According to an epidemiological study conducted in Russia, only 6.9% of the adults were previously diagnosed with asthma, whereas 25.7% of that same population reported asthma symptoms like wheezing or breathlessness that were not diagnosed earlier in their life [56] .…”
Section: Epidemiology and Different Factors Influencing Type-2 Asthmamentioning
confidence: 99%
“…This can partly be explained by the different points in time in which the studies took place, but also by different geographic locations, method of data collection, underlying populations, and diagnostic methods. For instance, Shilova et al [ 26 ] reported that 245 per 100,000 patients had active TB in Russia in 1999. Their data were collected from hospitals, where X-ray screening was done in only 57% of the total population and the quality of the bacteriology laboratory was lower compared to previous years.…”
Section: Discussionmentioning
confidence: 99%
“…Three papers were from Russia, and one was from Kazakhstan. Nugmanova D. et al [ 26 ] was the only study that reported asthma prevalence in Kazakhstan as doctor-diagnosed (19.5 per 1000, 2%) and as wheezing symptoms in adults (254 per 1000, 25%). Notably, this doctor-diagnosed prevalence was in between the rates in Ukraine and Azerbaijan (assessed in the same study, using the same methods), while the prevalence of wheezing symptoms was two-to-three times higher than the other two countries, suggestive of profound underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Similarly, in other western countries, a prevalence of “wheezing symptoms” of 74.4, 254.8, and 123.4/1000 adults in Ukraine, Kazakhstan, and Azerbaijan, was found, respectively. [28] A study in India found a prevalence of BA of 9.9% (95% CI = 7.53%–12.27%). [29]…”
Section: Discussionmentioning
confidence: 99%